Analysis of the genome data of Acinetobacter baumannii UOL-KIMZ-24, exhibiting multiple drug resistance through efflux pumpsGenebANK/NCBI. - Kiran Fatima; Syed Zeeshan Haider Naqvi; Hazrat Ali; Noor Hassan; Anam Saqib; Farheen Ansari; Sidrah Saleem; Shah Jahan; Mushtaq Ahmad (Data in Brief)
Acinetobacter baumannii is a well-known opportunistic pathogen, responsible for various nosocomial infections. A. baumannii UOL-KIMZ-24 was previously isolated from a clinical specimen, collected from Lahore General Hospital, Lahore (LGH), Pakistan, dated 3rd March, 2022. During the initial screening for antimicrobial susceptibility, the UOL-KIMZ-24 was found a multiple drug resistant (MDR) strain. However, the detailed genomic insights for genes e.g. responsible for exhibiting antibiotic resistance via efflux pumps, have not yet been reported from A. baumannii strains, recovered from LGH. The current research to fills this gap by isolating, whole genome sequencing and subsequent post-sequencing analysis for addressing and identifying the efflux pumps associated genes, responsible for multiple drug resistant in A. baumannii. In a hybrid approach, short reads were processed through Illumina platform, while long reads were sequenced by MinION MK1B sequencing technique. The assembled and annotated genome of the UOL-KIMZ-24 revealed that it has 4048631 bp genome size with 179 contigs, 38.9 % GC content, 3628 protein coding sequences, 80 tRNA and 7 rRNA. The analysis of antibiotic-resistance genes (AMR) depicted 27 genes. where the genes encoding efflux pumps such as adeABC, adeRS, adeJK, and adeMN were the more prominent. In addition, sequence typing (ST) study showed that UOL-KIMZ-24 strain lies in ST2, six prophage sequences and 73 virulence factors were also identified in the studied UOL-KIMZ-24. Such an all-inclusive study uncovered the genetic flexibility of UOL-KIMZ-24 genome for acquiring MDR against in-practice antibiotics.